1985
DOI: 10.1002/fld.1650050802
|View full text |Cite
|
Sign up to set email alerts
|

Laminar flow in a complex geometry: A comparison

Abstract: SUMMARYThis paper reports on the outcome of a workshop of the IAHR Working Group on Refined Modelling of Flows on the subject of computing laminar flows in complex geometries. Flow inside a channel with a smooth expansion was chosen by the organizers of the workshop as a suitable test case for assessing the capabilities of current numerical methods. The results obtained by fifteen participant groups are presented and compared against a suitable benchmark solution. The most important considerations that emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 9 publications
4
33
0
1
Order By: Relevance
“…5 are the results of Shu et al [14] using the DQ method with coordinate transformation and the benchmark solution of IAHR workshop given by Cliffe et al using a ®nite element method with results being grid-independent. Note that the results of Cliffe et al are shown in the paper of Napolitano et al [15]. It is seen from the ®gure that, the present results agree very well with the benchmark solution of the problem, and the accuracy of present results is even better than that given by Shu et al [14] using the DQ method.…”
Section: Nonlinear Differential Equationsupporting
confidence: 89%
See 2 more Smart Citations
“…5 are the results of Shu et al [14] using the DQ method with coordinate transformation and the benchmark solution of IAHR workshop given by Cliffe et al using a ®nite element method with results being grid-independent. Note that the results of Cliffe et al are shown in the paper of Napolitano et al [15]. It is seen from the ®gure that, the present results agree very well with the benchmark solution of the problem, and the accuracy of present results is even better than that given by Shu et al [14] using the DQ method.…”
Section: Nonlinear Differential Equationsupporting
confidence: 89%
“…For a general case, it is dif®cult to obtain the analytical solution of either Eq. (14) or (15). Thus, we need to further distribute the mesh points along each vertical line to discretize the y-derivatives in equation system (14) or (15), and pursue the numerical solution at these points.…”
Section: Numerical Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Para os resultados apresentados a seguir, foram considerados casos de escoamento laminar deágua (ρ = 1000.52 kg/m 3 , µ = 0.001 kg/ms, k = 0.597 W/m, C p = 4.1818 · 10 3 J/kg • C) dentro de um canal com expansão gradual, tal como ilustrado na figura 3.3 [69,70]. A geometria do canal depende do número de Reynolds, de tal forma que a expansão diminui a medida que o número de Reynolds aumenta.…”
Section: Resultsunclassified
“…These have been tested against benchmark results given in Ref. [13] as well as data for the friction factor under steady flow conditions reported in Refs. [14] and [15] (Figure 2).…”
Section: Methods Of Solutionmentioning
confidence: 99%